Values in Higher Education Teaching. - Pickering, Neil (Taylor & Francis, 2010)
Values in Higher Education Teaching explores the way in which teaching, research, learning and higher education are a values enterprise and that an exploration of values is necessary to work out the full purposes of a higher education to guide practices and help academics understand academic work. Values inform thinking and actions and although this is well recognized, values are seldom brought to the forefront of inquiries as practices in higher education are developed. This book argues that by putting values firmly on the agenda of those who teach, work and learn in higher education the academic profession can open up new spaces for value conversations and potentially transform the way in which they practice. Values in Higher Education Teaching is key reading for university lecturers, those with responsibility for leadership and management of higher education and postgraduates studying for higher degrees in higher education. There are few books that directly address the broad and complex question of values in teaching in higher education yet at the same time values are widely recognised as permeating all our practices. In this sense an accepted part of academic life remains in the realm of 'taken for granted' rather than being consciously and explicitly explored and practiced. The book deals with the idea of values in both a philosophical and practical manner. It is based on original research and uses both empirical data and theory to address teaching values in higher education and the current values of the higher education system. It explores what academics have valued historically in teaching and also addresses the major reforms of the last 20 years. Reforms have essentially changed the nature of western higher education but have made little real difference to the outcomes for student learning and society whereas teaching with values in all subjects has the potential to radically alter student experiences.